The Factors that Influenced Consumer’s Food Choice of Mobile Food Truck - Ideris, M. S. K; Nordin, N; Zainum, M. N. A; Mustafa, E; Zainol, N. A (2017)
Mobile food truck has become a popular choice and is trending among the people across the world. It provides similar service to fast food outlet- serving convenient, quick, tasty and mouth-watering food. Mobile food truck operates using miniature commercial kitchen and therefore it must meet the state’s sanitation requirements of a brick-and-mortar restaurant. Furthermore, the mobile food truck operators must comply with the additional local ordinances. Recent study found that there was an encouraging demand from the consumer for this type of food service. However, there is limited research that focuses on consumer’s choice in the context of “mobile food truck” especially in Malaysia. This study will look at the factors that influences the mobile food truck choice among consumers. The paper provides some recommendations on ways to improve the efficiency of the mobile food truck business by understanding the consumer food choice and improve the overall service offered by this sector.